Intersystem method of predicting the mass reproduction of sugar beet main pests - Диченко, О. Ю. (Scientific Progress & Innovations, 2012)
Historical information about mass reproduction of sugar beets main pests in the Left-bank Forest-steppe of Ukraine (name of kinds, years of mass reproductions in space and time) are given. On the basis of intersystem method of prediction algorithms of mass reproduction of sugar beet main pests, namely cutworml, beet webworm, cabbage moth and weevil are developed. And also prognosis of beginning the next flashes of their quantity on the period to 2018 year is developed.